Phenotypic Consequences of a Genetic Predisposition to Enhanced Nitric Oxide Signaling. Issue 3 (16th January 2018) - Emdin, Connor A.; Khera, Amit V.; Klarin, Derek; Natarajan, Pradeep; Zekavat, Seyedeh M.; Nomura, Akihiro; Haas, Mary; Aragam, Krishna; Ardissino, Diego; Wilson, James G.; Schunkert, Heribert; McPherson, Ruth; et al.
Abstract : Background: Nitric oxide signaling plays a key role in the regulation of vascular tone and platelet activation. Here, we seek to understand the impact of a genetic predisposition to enhanced nitric oxide signaling on risk for cardiovascular diseases, thus informing the potential utility of pharmacological stimulation of the nitric oxide pathway as a therapeutic strategy. Methods: We analyzed the association of common and rare genetic variants in 2 genes that mediate nitric oxide signaling (Nitric Oxide Synthase 3 [ NOS3 ] and Guanylate Cyclase 1, Soluble, Alpha 3 [ GUCY1A3 ]) with a range of human phenotypes. We selected 2 common variants (rs3918226 in NOS3 and rs7692387 in GUCY1A3 ) known to associate with increased NOS3 and GUCY1A3 expression and reduced mean arterial pressure, combined them into a genetic score, and standardized this exposure to a 5 mm Hg reduction in mean arterial pressure. Using individual-level data from 335 464 participants in the UK Biobank and summary association results from 7 large-scale genome-wide association studies, we examined the effect of this nitric oxide signaling score on cardiometabolic and other diseases. We also examined whether rare loss-of-function mutations in NOS3 and GUCY1A3 were associated with coronary heart disease using gene sequencing data from the Myocardial Infarction Genetics Consortium (n=27 815). Results: A genetic predisposition to enhanced nitric oxide signaling was associated with reduced risks of coronary heart disease (odds ratio, 0.37; 95% confidence interval [CI], 0.31-0.45; P =5.5*10 –26 ], peripheral arterial disease (odds ratio 0.42; 95% CI, 0.26-0.68; P =0.0005), and stroke (odds ratio, 0.53; 95% CI, 0.37-0.76; P =0.0006). In a mediation analysis, the effect of the genetic score on decreased coronary heart disease risk extended beyond its effect on blood pressure. Conversely, rare variants that inactivate the NOS3 or GUCY1A3 genes were associated with a 23 mm Hg higher systolic blood pressure (95% CI, 12-34; P =5.6*10 –5 ) and a 3-fold higher risk of coronary heart disease (odds ratio, 3.03; 95% CI, 1.29-7.12; P =0.01). Conclusions: A genetic predisposition to enhanced nitric oxide signaling is associated with reduced risks of coronary heart disease, peripheral arterial disease, and stroke. Pharmacological stimulation of nitric oxide signaling may prove useful in the prevention or treatment of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.